2013
DOI: 10.1111/sed.12058
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and architecture of a West Mediterranean Upper Pleistocene to Holocene coastal apron‐fan system

Abstract: The Quaternary deposits of tectonically stable areas are a powerful tool to investigate high-frequency climate variations (<10 ka) and to distinguish allogenic and autogenic factors controlling deposition. Therefore, an Upper Pleistocene-Holocene coastal apron-fan system in north-western Sardinia (Porto Palmas, Italy) was studied to investigate the relations between climate changes, sea-level fluctuations and sediment source-supply that controlled its development. The sedimentary sequence records the strong in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 88 publications
(140 reference statements)
1
23
0
Order By: Relevance
“…Overall, unit U3 is interpreted as a coastal strand plain with a dune‐field system migrating inland. This unit developed during a sea‐level rise culminating with a short period of high sea level (1.5 ± 1 m higher than at the present), tentatively referred to as the MIS 5c (about 100 ka) interstadial (Andreucci et al , ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Overall, unit U3 is interpreted as a coastal strand plain with a dune‐field system migrating inland. This unit developed during a sea‐level rise culminating with a short period of high sea level (1.5 ± 1 m higher than at the present), tentatively referred to as the MIS 5c (about 100 ka) interstadial (Andreucci et al , ).…”
Section: Resultsmentioning
confidence: 97%
“…The OSL dating method has been applied to terrigenous siliciclastic deposits of various aeolian, fluvial and shallow marine environments (Andreucci et al, 2012;Pascucci et al, 2014). This dating method is conventionally applied to quartz grains (Murray & Wintle, 2003); however, in recent years a method based on K-feldspar grains has been developed and applied successfully to coastal and alluvial deposits (Buylaert et al, 2012;Andreucci et al, 2014).…”
Section: Optically Stimulated Luminescence (Osl) Datingmentioning
confidence: 99%
“…Widespread coastal dune systems also developed during the Pleistocene on the northwest coast of Sardinia under cold and relatively dry conditions. They are interlayered by colluvial and paleosols, the oldest wind dominated system being dated from MIS 8 (Andreucci et al, 2010(Andreucci et al, , 2013Pascucci et al, 2014). It is suggested that this uppermost Orosei succession of aeolian origin was emplaced under the first cooling conditions of the Late Pliocene or the Early Pleistocene around 2.6 Ma (Ruddiman et al, 1989).…”
Section: Facies Association Of Aeolian Depositionmentioning
confidence: 96%
“…Particularly well‐developed carbonate aeolian systems occur in the Western Mediterranean region (Clemmensen et al ., ; Fornós et al ., ; Andreucci et al ., ). Quaternary successions with carbonate‐rich aeolian sand units crop out quasi‐continuously along the north‐west coast of Sardinia near the town of Alghero (Andreucci et al ., ,b, ). The aeolian units, which are lithified, occur along a cliffed coast and can be subdivided into cliff‐front dune accumulations and valley‐head sand ramps (Andreucci et al ., ; Fig.…”
Section: Evolution Of Aeolian Sand Systems Through Earth Historymentioning
confidence: 99%